Provitamin A biofortification of cassava enhances shelf life but reduces dry matter content of storage roots due to altered carbon partitioning into starch. Issue 6 (27th December 2017) - Beyene, Getu; Solomon, Felix R.; Chauhan, Raj D.; Gaitán‐Solis, Eliana; Narayanan, Narayanan; Gehan, Jackson; Siritunga, Dimuth; Stevens, Robyn L.; Jifon, John; Van Eck, Joyce; Linsler, Edward; Gehan, Malia; et al.
Summary: Storage roots of cassava ( Manihot esculenta Crantz), a major subsistence crop of sub‐Saharan Africa, are calorie rich but deficient in essential micronutrients, including provitamin A β‐carotene. In this study, β‐carotene concentrations in cassava storage roots were enhanced by co‐expression of transgenes for deoxy‐d ‐xylulose‐5‐phosphate synthase ( DXS ) and bacterial phytoene synthase ( crtB ), mediated by the patatin‐type 1 promoter. Storage roots harvested from field‐grown plants accumulated carotenoids to ≤50 μg/g DW, 15‐ to 20‐fold increases relative to roots from nontransgenic plants. Approximately 85%–90% of these carotenoids accumulated as all‐ trans ‐β‐carotene, the most nutritionally efficacious carotenoid. β‐Carotene‐accumulating storage roots displayed delayed onset of postharvest physiological deterioration, a major constraint limiting utilization of cassava products. Large metabolite changes were detected in β‐carotene‐enhanced storage roots. Most significantly, an inverse correlation was observed between β‐carotene and dry matter content, with reductions of 50%–60% of dry matter content in the highest carotenoid‐accumulating storage roots of different cultivars. Further analysis confirmed a concomitant reduction in starch content and increased levels of total fatty acids, triacylglycerols, soluble sugars and abscisic acid. Potato engineered to co‐express DXS and crtB displayed a similar correlation between β‐carotene accumulation, reduced dry matter and starch content and elevated oil and soluble sugars in tubers. Transcriptome analyses revealed a reduced expression of genes involved in starch biosynthesis including ADP‐glucose pyrophosphorylase genes in transgenic, carotene‐accumulating cassava roots relative to nontransgenic roots. These findings highlight unintended metabolic consequences of provitamin A biofortification of starch‐rich organs and point to strategies for redirecting metabolic flux to restore starch production.